Exploring the health risks of help-seeking military veterans living in different parts of the UK. Issue 1 (6th September 2017) - Ashwick, RL; Murphy, D
Abstract : Background: Little is known about the mental and physical health differences of treatment-seeking military veterans across the different nations that make up the UK. The aim of this research was to explore potential health differences in order to support better service planning. Methods: A random cross-sectional sample of treatment-seeking veterans residing in England, Scotland, Wales and Northern Ireland was identified from a national mental health charity. 403 veterans completed a questionnaire highlighting their demographics, mental health and physical health difficulties. The data were analysed using a multinomial logistic regression with England as the baseline comparison. Results: Help-seeking veterans residing in Northern Ireland tended to be older, have experienced less childhood adversity, joined the military after the age of 18 and took longer to seek help. Additionally, veterans from Northern Ireland had higher levels of obesity, sensory, mobility and systemic problems and a greater number of physical health conditions. Scottish and Welsh veterans had a higher risk of smoking and alcohol misuse. No differences were found in mental health presentations. Conclusion: The findings from this paper suggest that a greater focus needs to be placed on treating physical problems in Northern Irish veterans. Alcohol misuse should be addressed in more detail in treatment programmes, particularly in Scotland and Wales. As few differences were found in the mental health presentations, this suggests that standardised services are adequate.